The Effect of Games Simulation in Improving Secondary Students' Academic Performance - Dorji, Tshewang (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2022)
The main purpose of the study was to find out the effect of simulation games as an intervention program in teaching-learning economics to improve students' academic performance. The study adopts a mixed method. 27 (14 girls and 13 boys) grade twelve students in one higher secondary school participated in the study. The students were selected through non-probability convenient sampling techniques. The study revealed that the intervention program: and simulation games make concepts, ideas, and hypotheses easier to understand. The students have a positive opinion of simulation games used in teaching-learning. Simulation games make teaching-learning interesting, enjoyable, and fun. Through simulation games, students can score high marks on the class test. Students were engaged in self-assessment, self-awareness, self-monitoring, and reflective processes. However, the study revealed that simulation games are time-consuming and teachers need more time and effort for preparation and implementation. Simulation games are not always effective in teaching all micro and macroeconomics concepts.